Assessment of Intracellular Delivery Potential of Novel Sustainable Poly(δ-decalactone)-Based Micelles - Kuldeep Kumar Bansal; Ezgi Özliseli; Gaurav Kumar Saraogi; Jessica M. Rosenholm (MDPI AG, 2020)
Biodegradable polymers from renewable resources have attracted much attention in recent years within the biomedical field. Lately, poly(δ-decalactone) based copolymer micelles have emerged as a potential drug delivery carrier material as a sustainable alternative to fossil-based polymers. However, their intracellular drug delivery potential is not yet investigated and therefore, in this work, we report on the synthesis and cellular uptake efficiency of poly(δ-decalactone) based micelles with or without a targeting ligand. Folic acid was chosen as a model targeting ligand and Rhodamine B as a fluorescent tracer to demonstrate the straightforward functionalisation aspect of copolymers. The synthesis of block copolymers was accomplished by a combination of facile ring-opening polymerisation and click chemistry to retain the structure uniformity. The presence of folic acid on the surface of micelles with diameter ~150 nm upsurge the uptake efficiency by 1.6 fold on folate receptor overexpressing MDA-MB-231 cells indicating the attainment of targeting using ligand functionality. The drug delivery capability of these carriers was ascertained by using docetaxel as a model drug, whereby the in vitro cytotoxicity of the drug was significantly increased after incorporation in micelles 48 h post incubation. We have also investigated the possible endocytosis route of non-targeted micelles and found that caveolae-mediated endocytosis was the preferred route of uptake. This work strengthens the prospect of using novel bio-based poly(δ-decalactone) micelles as efficient multifunctional drug delivery nanocarriers towards medical applications.